Computational modelling of urban drainage network using LID alternatives in a sub-basin in the city of Maringa, Parana, Brazil - Camilo, Murilo; Nakahashi, Roberto Takeshi; Juliani, Bruno Henrique Toná; Vieira, Juliane Vier; Okawa, Cristhiane Michiko Passos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
With urbanization development, inundations and urban floods become more frequent. In the city of Maringa, Parana, this type of event is often observed in some specific dense urban locations, resulted by intense rainfall. In this context, the objective of this paper is to perform a computational modelling in the urban drainage network, most specifically in the sub-basin defined by the intersection of avenues Guaiapo and Palmares, in the city of Maringa, Parana, considering the current situation and with the application of Low Impact Development (LID) compensatory techniques. In this regard, the computational program SewerGEMS® was used to develop the scenarios simulations. The results shown that the actual network is undersized (Scenario 01), and it is proposed the adoption of LID compensatory measures (Scenarios 02, 03 and 04). The computational modelling in the elaboration of the scenarios was effective and it may support the municipal urban management with the implementation of an adequate and efficient system of stormwater management.